Changes in hormonal and lipid profile after a soccer match in male amateur players - Sotiropoulos, A.; Papapanagiotou, A.; Souglis, A.; Giosos, G.; Kotsis, G.; Bogdanis, G. C. (Serbian Journal of Sports Sciences, 2008)
This study examined the effects of a soccer match on plasma lipid profile, testosterone, cortisol and creatine kinase. Venous blood samples were taken before and after an official soccer match from twenty amateur soccer players (age: 24.5 ± 3). Blood was analyzed for total Cholesterol (T-C), high- (HDL) and low-density lipoproteins (LDL), serum triglycerides (TG), apolipoprotein B (APO-B) and AI (APO-AI), serum creatine phosphokinase (CPK) activity, testosterone (T), cortisol (C). CPK (p<0.001), C (p<0.05), APO-A (p=0.004) and HDL (p=0.009) level increased significantly after the match. Also, there was a significant decrease in LDL (p=0.002), APO-B (p= 0.000), TG (p=0.000), T-C (p= 0.000), LDL/HDL ratio (p= 0.001), T-C /HDL ratio (p=0.000), APO-A/APO-B ratio (p=0.019) and LDL/HDL ratio (p=0.000). T concentration decreased, while C concentration increased significantly, resulting in a >50% drop of T to C ratio (p=0.000). This data suggest that intermittent exercise of long duration, such as a soccer match, results in an acute antiatherogenic modification of lipid profile, possibly due to the high aerobic energy expenditure. The increase in C and decrease in T and the consequent large decrease of the T to C ratio, suggest that a soccer match places considerable stress on the endocrine system.